2017
DOI: 10.1016/j.smallrumres.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Predicting empty body weight in growing goats: A meta-analytic approach

Abstract: The objective of this study was to develop statistical models to predict empty body weight (EBW) by body weight (BW), testing the influence of sex (females, intact males or castrated males), type of diet (suckling or postweaning), and genotype (Saanen, ½ Boer × ½ Saanen, ¾ Boer × ¼ Saanen, and Indigenous goats). Individual records of 311 goats combined from 10 studies, with BW ranging from 4.3 to 47.4 kg were used. The EBW was computed as the BW at slaughter minus the weight of the contents of the digestive tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 49 publications
(59 reference statements)
1
12
0
Order By: Relevance
“…(2014), who reported puberty of female Saanen goats at 4.4 months. Considering the EBW, which is narrowly related to BW (Campos et al ., 2017), it was observed in the current study that the inflection point of intact and castrated males occurred at 4.1 months, whereas that of females occurred at 5.8 months. The inflection point represents the age in which the EBW growth rate is maximal, indicating changes in body fattening.…”
Section: Discussionsupporting
confidence: 50%
“…(2014), who reported puberty of female Saanen goats at 4.4 months. Considering the EBW, which is narrowly related to BW (Campos et al ., 2017), it was observed in the current study that the inflection point of intact and castrated males occurred at 4.1 months, whereas that of females occurred at 5.8 months. The inflection point represents the age in which the EBW growth rate is maximal, indicating changes in body fattening.…”
Section: Discussionsupporting
confidence: 50%
“…The empty body weight (EBW) was calculated as the difference between body weight at slaughter and the contents of the gastrointestinal tract and bladder. Considering that a robust estimative of EBW is critical in the comparative slaughter studies with goats, Campos et al (2017) gathered individual records of 311 growing goats to develop empirical models to predict EBW from BW. They found that there is no need to use different models for goats of different sex; however, different models are required to predict EBW from BW for suckling and post-weaning Saanen goats.…”
Section: General Methodological Aspects When Applying Cnes To Goatsmentioning
confidence: 99%
“…They found that there is no need to use different models for goats of different sex; however, different models are required to predict EBW from BW for suckling and post-weaning Saanen goats. In general, suckling goats show a decreasing relationship between EBW and BW, oppositely it remained relatively constant in post-weaning goats ( Campos et al, 2017 ). Moreover, goats of different genotypes have different gastrointestinal relative capacity, which implied in the need of using different empirical model according to the goat genotype ( Campos et al, 2017 ).…”
Section: General Methodological Aspects When Applying Cnes To Goatsmentioning
confidence: 99%
“…Several studies used many mathematical functions to represent growth performance over time in goats [6,[24][25][26][27]. For example, Campos et al [6] studied the prediction of empty body weight (the weight of goats minus the digestive tract contents). In avian, the mathematical models were used to predict the growth rate and size of the alimentary tract [28].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing body weight and feed efficiency are of importance for profitable goat farming [ 4 ]. The growth of body weight and body weight measurements depends on the digestive tract’s development [ 5 , 6 ]. In goats, the gastrointestinal tract as a percentage of the empty body weight increased from 13 up to 27% as they grew, in which the rumen contributed most to the growth [ 6 ].…”
Section: Introductionmentioning
confidence: 99%